Implementation of Boarding School-Based Educational Institution Management in Character Building - Erlinda Muflikhah; Diningrum Citraningsih (Jawda: Journal of Islamic Education Management, 2025)
This research aims to analyze in depth the process of boarding school-based educational management in forming a positive cultural character of students at Trenmatika IBS School Bekasi. The study uses a qualitative approach with a case study method. Data collection techniques were conducted through in-depth interviews with the school principal, teachers, musyrif (mentors), students, and parents, as well as observation of daily activities and documentation of school programs. The research findings show that educational management is implemented in a structured manner through the stages of planning, implementation, supervision, and evaluation, which are integrated with religious and character values. Programs such as Sholat Khusyu' (prayer with deep concentration), Tahsinul Qur’an (improving Qur'an recitation), time management, and environmental cleanliness are part of a habituation strategy that shapes the discipline, responsibility, and spirituality of students. Supervision is carried out continuously with a reward and punishment system and parental involvement through communication forums. These findings indicate that effective and participatory management can create an educational environment that supports holistic character building. The limitation of this research lies in the untapped aspects of quantitative measurement and a more in-depth role of the family. The implications of this research can serve as a reference for the development of character education management in other boarding school environments.